Disadvantageous Decision-Making as a Predictor of Drop-Out among Cocaine-Dependent Individuals in Long-Term Residential Treatment - Stevens, Laura; Betanzos-Espinosa, Patricia; Crunelle, Cleo L.; Vergara-Moragues, Esperanza; Roeyers, Herbert; Lozano Rojas, Óscar; Geert, Dom; González-Saiz, Francisco; Vanderplasschen, Wouter; Verdejo-García, Antonio; Pérez-García, Miguel (Frontier in Psychiatry, 2017)
The treatment of cocaine-dependent individuals (CDI) is substantially challenged by high drop-out rates, raising questions regarding contributing factors. Recently, a number of studies have highlighted the potential of greater focus on the clinical significance of neurocognitive impairments in treatment-seeking cocaine users. In the present study, we hypothesized that disadvantageous decision-making would be one such factor placing CDI at greater risk for treatment drop-out.
Keywords: decision-making; drop-out; treatment retention; addiction treatment outcomes; cocaine dependence; Scopus